Decoding ABA and osmostress signalling in plants from an evolutionary point of view. (24th September 2020) - Komatsu, Kenji; Takezawa, Daisuke; Sakata, Yoichi
Abstract: The plant hormone abscisic acid (ABA) is fundamental for land plant adaptation to water‐limited conditions. Osmostress, such as drought, induces ABA accumulation in angiosperms, triggering physiological responses such as stomata closure. The core components of angiosperm ABA signalling are soluble ABA receptors, group A protein phosphatase type 2C and SNF1‐related protein kinase2 (SnRK2). ABA also has various functions in non‐angiosperms, however, suggesting that its role in adaptation to land may not have been angiosperm‐specific. Indeed, among land plants, the core ABA signalling components are evolutionarily conserved, implying their presence in a common ancestor. Results of ongoing functional genomics studies of ABA signalling components in bryophytes and algae have expanded our understanding of the evolutionary role of ABA signalling, with genome sequencing uncovering the ABA core module even in algae. In this review, we describe recent discoveries involving the ABA core module in non‐angiosperms, tracing the footprints of how ABA evolved as a phytohormone. We also cover the latest findings on Raf‐like kinases as upstream regulators of the core ABA module component SnRK2. Finally, we discuss the origin of ABA signalling from an evolutionary perspective. Abstract : The plant hormone abscisic acid (ABA) is important in the adaptation of plants to drought conditions. Among land plants, ABA core signalling components, including the soluble ABA receptors PYR/PYL/RCAR, group A protein phosphatase type 2C and SNF1‐related protein kinase 2 (SnRK2), are evolutionarily conserved. In this review, we focus on recent comparative studies of ABA core signalling components between angiosperms and non‐angiosperms, such as bryophytes and algae, that allow us to trace the evolution of ABA as a phytohormone. We also describe recent progress in elucidating the mechanism by which B‐Raf kinases activate SnRK2.